Why Pakistan Must Lead in Regional Multi-Omics Research for Precision Medicine - SHUJA, NAVEED (Pakistan Journal of Medical & Health Sciences, 2025)
Precision medicine has emerged as one of the most transformative movements in global healthcare, shifting the clinical emphasis from generalized treatments to highly individualized interventions informed by molecular data¹. At the core of this revolution lies multi-omics research, the integration of genomics, transcriptomics, proteomics, metabolomics, epigenomics, and microbiomics². For a country as genetically diverse and medically burdened as Pakistan, leading this domain is not an option it is an urgent requirement³. Pakistan’s population structure, disease epidemiology, and regional position create a compelling case for establishing itself as the central hub of multi-omics innovation in South Asia and beyond⁴. Pakistan’s Distinct Population Structure and Its Scientific Potential Pakistan hosts one of the world’s most genetically diverse populations, marked by high consanguinity rates, clustered regional variants, and distinct disease patterns that differ substantially from Western populations⁵. Relying on foreign genomic datasets risks scientific inaccuracy, misdiagnosis, and suboptimal treatment responses because those datasets do not reflect Pakistan’s biological realities⁶. Local multi-omics research can uncover genetic mutations unique to Pakistani subpopulations, early biomarkers for metabolic and cardiovascular disorders, and molecular signatures for cancers and infectious diseases⁷. These highly specific insights cannot be imported or approximated from international studies⁸. They must be generated locally through structured, high-quality omics programs⁹ Pakistan’s Opportunity to Become a Regional Biomedical Leader Geographically, Pakistan lies at a strategic intersection connecting South Asia, Central Asia, and the Middle East regions with shared demographic structures but limited representation in global omics repositories¹⁰. Pakistan’s leadership can therefore provide a regional ecosystem that supports data generation, analysis, and translational innovation¹¹. Establishing national multi-omics platforms will attract international research collaboration, physician-scientist partnerships, biotech companies, and large-scale investment¹². As neighboring countries increasingly seek population-specific precision medicine tools, Pakistan can position itself as the regional center for multi-omics expertise and clinical validation¹³. Transforming Clinical Practice Through Multi-Omics Integration Pakistan faces a growing burden of non-communicable diseases, particularly diabetes, cardiovascular disorders, cancer, autoimmune conditions, and infectious diseases with high morbidity¹⁴. Multi-omics technology has the potential to reshape clinical practice by enabling early diagnosis through molecular signatures, disease prediction using integrative biomarker profiles, personalized drug response assessments, and better antimicrobial stewardship through resistance-omics¹⁵. In oncology, multi-omics can provide deeper insights into colorectal cancer, breast cancer, cervical cancer, and hepatocellular carcinoma, allowing clinicians to design treatment plans based on tumor-specific molecular patterns⁶. In cardiometabolic diseases, integrating transcriptomics and metabolomics can identify early markers long before clinical symptoms emerge⁹. These advancements would shift Pakistan from reactive treatment to proactive, preventive, and personalized medicine¹¹. National Biosecurity and Genomic Independence Modern biosecurity is deeply tied to a nation’s ability to generate and control its own genomic datasets¹². Countries that lack local sequencing and multi-omics capacity remain dependent on foreign laboratories for disease characterization, pathogen typing, and therapeutic discovery¹⁴. Pakistan must secure its biological independence by creating robust omics infrastructure capable of rapid pathogen identification, vaccine target prediction, drug-resistance mapping, and characterization of emerging infectious threats⁷. Local control of biological data ensures that sensitive genomic information remains protected within national boundaries and supports the domestically informed development of diagnostics and therapeutics¹⁵. Economic Growth and the Rise of a Local Biotechnology Sector A strong multi-omics ecosystem will stimulate economic expansion by creating new opportunities in biotechnology, pharmaceutical development, diagnostic kit production, and academic–industry partnerships⁸. Trained professionals in molecular biology, bioinformatics, systems biology, data analytics, and computational genomics will be increasingly in demand¹⁰. Industry-quality omics centers will attract investment from pharmaceutical companies interested in developing population-specific therapies¹³. Pakistan can also generate regionally relevant biomarker panels, AI-driven clinical prediction models, and cost-effective diagnostic assays that can be exported across South Asia, the Middle East, and Africa¹⁴. Precision medicine is rapidly becoming an economic engine, and Pakistan has both the population base and scientific capacity to benefit enormously¹¹. Building the Necessary National Infrastructure To lead in multi-omics research, Pakistan must develop national centers equipped with next-generation sequencing platforms, mass spectrometry-based proteomics systems, metabolomic analyzers, biobanking facilities, and secure high-performance computing frameworks⁶. Tertiary-care hospitals should be connected to research universities through structured multi-institutional networks that integrate patient data, biospecimens, and outcome records¹². Training programs must be expanded to prepare scientists, clinicians, and researchers in advanced diagnostics, computational analysis, and translational systems biology¹⁵. Ethical and regulatory frameworks must be strengthened to ensure structured biobank governance, patient data protection, and transparent scientific workflows that align with international best practices¹⁰. CONCLUSION Pakistan stands at a decisive scientific crossroads¹. Its population genetics, disease epidemiology, and geographic significance make it uniquely positioned to become the regional leader in multi-omics research³. By prioritizing investment in national omics platforms, strengthening academic and clinical collaborations, ensuring secure data governance, and nurturing the next generation of molecular scientists⁵, Pakistan can fundamentally transform its healthcare landscape⁴. Precision medicine begins with understanding one’s own genome and biological identity². If Pakistan takes bold action today, it will shape a healthier, more scientifically empowered, and globally recognized future one driven by local discovery and regional leadership in multi-omics and precision medicine¹¹.